2016
DOI: 10.20517/2394-5079.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Can gender predict virological response to standard antiviral therapy for chronic hepatitis C? A retrospective study

Abstract: Aim:The liver is a sexually dimorphic organ presenting gender differences in its metabolism, functions, enzyme activity, membrane lipid composition and immune response. This paper aimed to assess whether gender may predict virological response to standard antiviral therapy in subjects with chronic hepatitis C (CHC). Methods: The authors retrospectively analyzed 100 patients with genotype 1 CHC (55 men, 45 women), who performed standard antiviral therapy (interferon and ribavirin for 12 months) in the period 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Most of the treatment-experienced were treated with IFN-based regimens, to which, in the under-50 age group, men also responded worse than women, so a higher percentage of them required antiviral retherapy. 50 In our analysis, women of childbearing age were significantly less burdened by comorbidities than men (40% vs. 44%) and were significantly less likely to require comedications (37% vs. 45%). In this regard, it is difficult for us to compare our results with other studies because, to the best of our knowledge, no research comparing patients at age below 50 years treated for HCV by sex has yet been published, while data on the population prevalence of comorbidities in this age group are disparate.…”
Section: Ta B L Ementioning
confidence: 64%
See 1 more Smart Citation
“…Most of the treatment-experienced were treated with IFN-based regimens, to which, in the under-50 age group, men also responded worse than women, so a higher percentage of them required antiviral retherapy. 50 In our analysis, women of childbearing age were significantly less burdened by comorbidities than men (40% vs. 44%) and were significantly less likely to require comedications (37% vs. 45%). In this regard, it is difficult for us to compare our results with other studies because, to the best of our knowledge, no research comparing patients at age below 50 years treated for HCV by sex has yet been published, while data on the population prevalence of comorbidities in this age group are disparate.…”
Section: Ta B L Ementioning
confidence: 64%
“…Another difference between the treated patient populations recognised in our analysis was the significantly higher proportion of men with a history of previous therapy failure compared to women. Most of the treatment‐experienced were treated with IFN‐based regimens, to which, in the under‐50 age group, men also responded worse than women, so a higher percentage of them required antiviral retherapy 50 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of viral clearance, the number of studies in the past showed age and gender disparity after Interferon therapy. In one study by Belci et al [15], there was a significantly higher SVR in females aged ˂50 years. Likewise, Bhattacharya et al found a higher SVR in premenopausal women [16].…”
Section: Discussionmentioning
confidence: 99%
“…So in this study similar results were found. 41,42 There were 13 patients who discontinued the therapy. Discontinuation of therapy was mainly due to either side effects of the drugs or any other co-morbidity that imposed additional stress on the patient and led to inability to tolerate the therapy.…”
Section: Discussionmentioning
confidence: 99%